THE INFLUENCE OF LEADERSHIP ON LPD GROWTH WITH CULTURE AS A CODING VARIABLE - Ketut Gunawan (Jurnal MEBIS (Manajemen dan Bisnis), 2022)
This study aims to determine the influence of leadership on the growth of Village Credit Institutions (LPD) in Bali and whether the Tri Hita Karana (THK) culture can moderate these influences. The leadership variables adopt eight leadership traits of Asta Brata which include: Indra Brata, Yama Brata, Surya Brata, Candra Brata, Vayu Brata, Bhumi Brata, Varuna Brata and Kwera Brata. Tri Hita Karana culture adopts a philosophy that includes Parhyangan, Pawongan and Palemahan. LPD growth adopts M. Porter's industrial growth strength model which includes: threat of new entrants, supply strength of suppliers, supply strength of buyers, threat of substitution products, and competition. Data collection uses questionnaire techniques and is analyzed with regression analysis and moderator regression analysis. The results of the data analysis show that leadership has a positive and significant effect on LPD growth, and THK culture strengthens the influence of leadership on LPD growth in Bali.